Religion og etikk i skole og barnehage - Afset, Bente; Redse, Arne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
School and kindergarten are central arenas for issues concerning values and ethics. The authors ask: What does students in junior high school learn about the relationship between science and religion? How do students in teacher education relate to the question of sex and equality? How do you communicate values and ethics in kindergarten? In this antology the authors looks to answer these question, and many more. This book is relevant for anyone who works in schools and kindergartens.